Recent Advances in Gadolinium Based Contrast Agents for Bioimaging Applications - Atiya Fatima; Md. Wasi Ahmad; Abdullah Khamis Ali Al Saidi; Arup Choudhury; Yongmin Chang; Gang Ho Lee (Nanomaterials, 2021)
Gadolinium (Gd) based contrast agents (CAs) (Gd-CAs) represent one of the most advanced developments in the application of Gd for magnetic resonance imaging (MRI). Current challenges with existing CAs generated an urgent requirement to develop multimodal CAs with good biocompatibility, low toxicity, and prolonged circulation time. This review discussed the Gd-CAs used in bioimaging applications, addressing their advantages and limitations. Future research is required to establish the safety, efficacy and theragnostic capabilities of Gd-CAs. Nevertheless, these Gd-CAs offer extraordinary potential as imaging CAs and promise to benefit bioimaging applications significantly.